Pengaruh Arsitektur Neo-Vernakular terhadap Identitas Budaya Lokal (Studi Kasus : Balai Pemuda Surabaya) - Achmad Adam Firmansyah; Ami Arfianti (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
This study explores the contribution of neo-vernacular architecture to the formation and preservation of local cultural identity, with a case study of the Balai Pemuda building in Surabaya. Neo-vernacular architecture is recognized as a design approach that combines traditional elements with modern styles, making it relevant in the context of cultural preservation in urban environments. This research employs a qualitative descriptive method with data collection techniques including case studies, field observations, visual documentation, and in-depth interviews. Findings reveal that elements such as roof forms, decorative motifs, and spatial arrangements in Balai Pemuda reflect the cultural values of Surabaya. The integration of traditional elements within a modern design framework not only enhances the architectural character of the building but also raises public awareness about the importance of preserving cultural heritage. The results of this study contribute to the discourse on architectural design that respects cultural context and promotes the creation of sustainable, contextual, and culturally enriched architecture.